1997
DOI: 10.1021/bi962538g
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and Thermal Denaturation of Apocalmodulin:  Role of Electrostatic Mutations

Abstract: Scanning microcalorimetry and circular dichroism were used to study conformational state and heat denaturation of Ca2+-free synthetic calmodulin (SynCaM) and three charge reversal mutants. We produced evidence for the major role of the electrostatic potential in the stability and flexibility of SynCaM. The substitution of 118DEE120 by 118KKK120 (SynCaM12A) does not influence the flexibility of the protein; the replacement of 82EEE84 by 82KKK84 (SynCaM8) decreases its level, while the combination of these two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
77
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 42 publications
10
77
0
Order By: Relevance
“…It was found that the stoichiometry of CaMKI/Ca 2ϩ -CaM complex formation in sodium cacodylate buffer is on the order of 0.8:1. Somewhat peculiar effects of cacodylate on the conformation and stability of calmodulin have also been previously observed (54).…”
Section: Resultssupporting
confidence: 53%
“…It was found that the stoichiometry of CaMKI/Ca 2ϩ -CaM complex formation in sodium cacodylate buffer is on the order of 0.8:1. Somewhat peculiar effects of cacodylate on the conformation and stability of calmodulin have also been previously observed (54).…”
Section: Resultssupporting
confidence: 53%
“…The reversibility of unfolding was checked routinely by sample reheating after cooling in the calorimetric cell. The calorimetric denaturation enthalpy (⌬H cal ) and the partial molar heat capacity of the protein (C p ) were determined as described elsewhere (13), assuming that the molecular mass of SynCaM is 16628 Da and the partial specific volume is 0.72 cm 3 g Ϫ1 (7). To analyze functions of excess heat capacity, the MicroCal Origin software was used.…”
Section: Methodsmentioning
confidence: 99%
“…There was no ITC signal upon apoSynCaM titration with EGTA. Cacodylate buffer (10 mM) was used because we have shown that this buffer concentration does not induce a major change in the secondary structure of apoprotein (7). Some experiments were done in 50 mM Hepes.…”
Section: Rs20mentioning
confidence: 99%
See 1 more Smart Citation
“…The instrument was calibrated with (+)-10-camphorsulfonic acid, assuming [θ]291 = 7820 deg cm 2 dmol −1 (Schippers & Deckers 1981) and with JASCO standard non-hydroscopic ammonium (+)-10-camphorsulfonate, assuming [θ]290.5 = 7910 deg cm 2 dmol −1 (Takakuwa et al 1985). Noise in the data was smoothed using the JASCO J-715 software, including the fast Fourier-transform noise reduction routine which allows the enhancement of most noisy spectra without distorting their peak shapes (Protasevich et al 1997). …”
Section: Stopped-flow Kinetic Measurementsmentioning
confidence: 99%